Cassava and sweet potato network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The scourge of droughts in the southern African region during recent years has underscored the importance of cassava and sweet potato, not only as famine relief crops but also as crops with strong potential for diversification and improving food...